Ecology : - Molles, Manuel C (McGraw-Hill, 2002)
The book consists of 23 chapters devided into 6 section. The first section focus on natural history, the second about individuals. The third focus on population ecology. The fourth and the 5th express the interactions anf communities and ecosystems. The last section of the book examines the large-scale ecology